2022
DOI: 10.1039/d2ta03475a
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional surface modification coupled with oxygen defect engineering enables high performance Li-rich cathodes

Abstract: Through the total cyclization of polyacrylonitrile, a bifunctional surface and abundant oxygen defects were constructed on the lithium-rich cathode, leading to an excellent electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…It is also reported that oxygen defects can ensure a high degree of oxygen redox. 39 Furthermore, it is claimed that the phase transitions and volume variation are very sensitive to the impurity levels of LiCoO 2 particles and it can be used as a quality check for the synthetic LiCoO 2 material. 13,40 increases after more than 62.5-75% removal of Li (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is also reported that oxygen defects can ensure a high degree of oxygen redox. 39 Furthermore, it is claimed that the phase transitions and volume variation are very sensitive to the impurity levels of LiCoO 2 particles and it can be used as a quality check for the synthetic LiCoO 2 material. 13,40 increases after more than 62.5-75% removal of Li (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The structural deterioration of the material will gradually extend from the surface to the interior, eventually exacerbating the performance decay of the material. [6] To solve the above problems, a variety of modification means have been proposed, such as element doping, [7] surface modification [8] and pretreatment, [9] etc. Among them, surface coating has become one of the most effective modification methods to improve the interfacial stability of the material.…”
Section: Introductionmentioning
confidence: 99%
“…It attributed to PMO coating layers can effectively reduce the side reaction with electrolyte, increase the conductivity of Li + and effectively reduce the mixing of Li + /Ni 2 + , maintain the stability of structure, [9] and greatly increase the reversible capacity of LLOs. [10] Chaoliang Zheng et al [11] firstly propose to coat a layer of completely cyclized polyacrylonitrile on the surface of the Lirich cathode Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O 2 , which forms a spinel layer and abundant oxygen vacancies on the surface to alleviate the above problems. As shown by the superior electrochemical performance, the specific capacity of the modified material was increased to 175 mAh g À 1 with a capacity retention rate of 73.7 % after 275 cycles at 0.5 C. Moreover, other coating oxides have also been used for surface coating modification of LLOs, which can help to improve the electrochemical performance of LLOs.…”
Section: Introductionmentioning
confidence: 99%